A Review and Reassessment of Travertine Classification - Pentecost, Allan; Viles, Heather (Géographie physique et Quaternaire, 1994)
ABSTRACTThis paper provides a review of the classification of travertines with emphasis on their morphology. Three criteria are used to describe them: geochemistry, microfabric and morphology. Geochemically, travertines may be divided into two groups, the meteogene travertines, where the carrier carbon dioxide originates in the soil and epigean atmosphere, and the thermal (thermogene) travertines where the carbon dioxide comes from thermally generated sources. Many travertine fabrics are influenced by bacteria and plants. These include 'stromatolitic' forms, many oncoids, shrubs, tufts, mats and moss travertines. Morphologically, travertines are conveniently divided into autochthonous (spring mounds and ridges, cascades, barrages, fluvial and lacustrine crusts, paludal deposits and cemented rudites) and the allochthonous or clastic travertines (valley-fills, back-barrage deposits, alluvial cones). Travertine deposits often include a wide range of fabrics and morphologies in one system. They are influenced locally by discharge, slope, vegetation, climate and human activity. Intergradations occur, both within travertine types but also with other freshwater deposits, e.g. calcrete and lake chalk. The influence of travertine deposition on the local hydrology and geomorphology is also discussed. The review emphasises the significance of scale and hydrology and aims to provide a unified scheme of travertine classification.